Estimation of influenza incidence and analysis of epidemic characteristics from 2009 to 2022 in Zhejiang Province, China - Wu, Haocheng; Xue, Ming; Wu, Chen; Ding, Zheyuan; Wang, Xinyi; Fu, Tianyin; Yang, Ke; Lin, Junfen; Lu, Qinbao (Frontiers in Public Health, 2023)
Background: Influenza infections annually cause a substantial burden, however, the number of reported cases of influenza may significantly underestimate the actual prevalence of influenza. Methods: The randomforest analysis , the moving epidemic method(MEM) ,the joinpoint regression analysis and the wavelet analysis was applied. Results: The number of estimated influenza cases from 2009 to 2018 were 743,449, 47,635, 89,026, 13,2647, 69,218, 190,099, 204,606, 190,763, 267,168 and 364,809, respectively. The total number of estimated influenza cases is 12.11 times of the number of reported cases. The intensity level of estimated incidence from epidemic threshold to very high intensity threshold were 18.94 cases per 100,000, 24.14 cases per 100,000, 141.55 cases per 100,000, 309.34 cases per 100,000, respectively. The average power was significant on the 6-month scale ,1-year scale, 115-weeks scale and the average power of the first two cycles is significantly higher than that of other cycles. In the period from 20th week to 35th week, the person correlation coefficients between the time series of influenza onset and the positive rate of pathogens including A (H1N1)pdm2009, A(H3N2), B(Victoria) and B(Yamagata) was -0.089(P=0.021), 0.497(P <0.001), -0.062(P=0.109) and -0.084(P =0.029), respectively. In the period from 36th week of the first year to 19th week of the next year, the person correlation coefficients between the time series of influenza onset and the positive rate of pathogens including A (H1N1)pdm2009, A(H3N2), B(Victoria) and B(Yamagata) was 0.516(P<0.001), 0.148(P <0.001), 0.292(P <0.001) and 0.271(P <0.001), respectively. Conclusions: The actual incidence level of influenza is much higher than the current reported number. The intensity level of estimated incidence from epidemic threshold to very high intensity threshold were calculated, which provides a quantitative standard for judging the influenza prevalence level in the future. The incidence of influenza showed semiannual peaks of activity, including a major peak from December to January of the next year followed by a peak in summer. Furthermore. The driving factors of influenza peak have been preliminarily explored, while the peak in summer was mainly driven by pathogens of A(H3N2) and the peak in winter was driven by various pathogens alternately.